YIELD AND FIBER QUALITY OF COTTON CULTIVARS IN RESPONSE TO SHADING (Colloquium Agrariae. ISSN: 1809-8215, 2018)
Shading is an environmental stress that affects cotton production areas, especially under tropical and rainfed conditions. The aim of this research was to evaluate the tolerance of cotton cultivars to shading. A field experiment was carried out in Primavera do Leste - MT, Brazil in the 2014 growing season. The experimental design was a 2 x 4 factorial (shading x cultivars) in randomized blocks with 4 replications. Cotton cultivars include late (TMG 82WS) and mid-early (IMA 5675B2RF, IMA 5672B2RF and IMA 5822B2RF). Shading (50% light reduction) was imposed at flowering onset (F2/F3 - Stage) for 2 weeks. Node number, boll number and fiber yield decreased by shading by 18,5, 36 and 25% on mid-early cultivars (average), respectively, as compared to the late cultivar. Boll weight was not affected by shading. For fiber quality parameters, shading reduced micronaire by 6,0 in the mid-early cultivars and fiber strength was increased by 6.4% on cultivar IMA 5672B2RF under shading and it was associated with the lowest boll number in such cultivar. It was concluded that in a season with no water or temperature limitation, the late cultivar could recovery the yield in the top of the plant. Shading decrease micronaire index, but the response depends on cultivar. Fiber properties such as length and strength were affected by shading but this response was related to the number of fruits retained by the plant.